Physical interactions of fish protamine and antisepsis peptide drugs with bacterial membranes revealed by combination of specular x-ray reflectivity and grazing-incidence x-ray fluorescence - Abuillan, Wasim; Schneck, Emanuel; Körner, Alexander; Brandenburg, Klaus; Gutsmann, Thomas; Gill, Tom; Vorobiev, Alexei; Konovalov, Oleg; Tanaka, Motomu (Physical review. E, Statistical, nonlinear, and soft matter physics, 2013)
As a defined model of outer membranes of gram negative bacteria, we investigated the interaction of monolayers of lipopolysacchrides from Salmonella enterica rough strains R90 (LPS Ra) with natural and synthetic peptides. The fine structures perpendicular to the membrane plane and the ion distribution near the interface were determined by specular x-ray reflectivity (XRR) and grazing-incidence x-ray fluorescence (GIXF) in the presence and absence of divalent cations. The unique combination of XRR and GIXF allows for the quantitative identification of different modes of interactions in a high spatial resolution, which cannot be assessed by other experimental methods. Natural fish protamine disrupts the stratified membrane structures in the absence of Ca2+ ions, while staying away from the membrane surface in the presence of Ca2+ ions. In contrast, synthetic antisepsis peptide Pep 19-2.5 weakly adsorbs to the membrane and stays near the uncharged sugar units even in the absence of Ca2+. In the presence of Ca2+, Pep 19-2.5 can reach the negatively charged inner core without destroying the barrier capability against ions.